Strategi Enterprise Arsitektur Teknologi Informasi Studi Kasus PT. Hikmah Pointau - Moeng Sakmar (Universitas Mercu Buana Yogyakarta, 2023)
The information technology used in the company is expected to provide an advantage in increasingly competitive competition over time that coincides with the development of industries in all sectors. PT. Hikmah Pointau is a bottled drinking water company (AMDK) by producing mineral water with various sizes of packaging. The production and business process combines synergy between technology and information systems to achieve the best service to consumers even though it is not yet optimized. Building a mature and integrated system in the company requires careful and measurable planning in order for business goals and customer satisfaction to be achieved. Enterprise Architecture (EA) is able to plan the overall system in the company which includes organizational and business aspects. EA’s can be used in terms of analysis, integration and documentation of the overall architecture of the organization as well as the company. In this proposal, TOGAF Framework is used to formulate and create blueprint architecture technology and SWOT analysis to support business and organizational activities to achieve the best business goals and services